The Spiderwick Chronicles: The Wrath of Mulgarath - Book 5 - DiTerlizzi, Tony; Black, Holly (New York : Simon & Schuster Books for Young Readers, 2004)
The three children are given their most frightful and challenging test yet, when they return home they find that the house has been ransacked and much out of place - including the Field Guide and their mother.
Ages 7 and up.
Keywords: Dwarfs -- Fiction; Goblins -- Fiction; Brothers and sisters -- Fiction; Dwarfs -- Fiction; Goblins -- Fiction; Brothers and sisters -- Fiction; Fantasy